Pre-Exposure Prophylaxis (PrEP) Awareness Is Low Among Heterosexual People of Color Who Might Benefit From PrEP in Philadelphia. (May 2019) - Roth, Alexis M.; Tran, Nguyen K.; Piecara, Brogan L.; Shinefeld, Jennifer; Brady, Kathleen A.
Introduction: We assessed awareness of pre-exposure prophylaxis (PrEP) among HIV-negative Black and Latinx persons living in the Philadelphia Metropolitan Statistical Area.Methods: Using chi-square and Wilcoxon rank-sum tests, we analyzed data from the 2016 heterosexual cycle of the National HIV Behavioral Surveillance system to assess how sociodemographic factors, health care utilization, and risk behaviors affected PrEP awareness.Results: Participants (n = 472) were predominately Black, non-Hispanic (88.1%) with a median age of 41.5 years. Most participants reported having a usual source of medical care (92.1%) and seeing a medical provider within 12 months (87.0%). However, PrEP awareness was low in this sample (4.9%) and was lower among those who had a medical visit compared with those who had not ( P < .01).Conclusion: Current Centers for Disease Control and Prevention clinical guidelines suggest that providers counsel high-risk patients about PrEP. Our data suggest that this is not happening with people of color in Philadelphia. Interventions targeting medical providers working with HIV-risk people of color may be appropriate.